2021
DOI: 10.1515/revneuro-2021-0054
|View full text |Cite
|
Sign up to set email alerts
|

New insights into neural networks of error monitoring and clinical implications: a systematic review of ERP studies in neurological diseases

Abstract: Error monitoring allows for the efficient performance of goal-directed behaviors and successful learning. Furthermore, error monitoring as a metacognitive ability may play a crucial role for neuropsychological interventions, such as rehabilitation. In the past decades, research has suggested two electrophysiological markers for error monitoring: the error-related negativity (ERN) and the error positivity (Pe), thought to reflect, respectively, error detection and error awareness. Studies on several neurologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 157 publications
(249 reference statements)
2
9
0
Order By: Relevance
“…This evidence is in line with findings in other clinical populations, such as patients with ACC lesion (Maier et al, 2015; for systematic reviews see Lenzoni et al, 2021 andPezzetta et al, 2021) in which the Pebut not the ERN/theta -was unaltered. It was previously found that patients with lateral prefrontal lesion which extended to the insula had reduced Pe response (Ullsperger et al, 2002;Ullsperger & von Cramon, 2006), suggesting that the activity associated to the Pe activity might engage a neural network involving not only the ACC, but also anterior insula and somatosensory areas (Ullsperger et al, 2010), that may be spared in PD.…”
Section: Dopamine Does Not Modulate the Opesupporting
confidence: 89%
See 2 more Smart Citations
“…This evidence is in line with findings in other clinical populations, such as patients with ACC lesion (Maier et al, 2015; for systematic reviews see Lenzoni et al, 2021 andPezzetta et al, 2021) in which the Pebut not the ERN/theta -was unaltered. It was previously found that patients with lateral prefrontal lesion which extended to the insula had reduced Pe response (Ullsperger et al, 2002;Ullsperger & von Cramon, 2006), suggesting that the activity associated to the Pe activity might engage a neural network involving not only the ACC, but also anterior insula and somatosensory areas (Ullsperger et al, 2010), that may be spared in PD.…”
Section: Dopamine Does Not Modulate the Opesupporting
confidence: 89%
“…From a neuroanatomical and functional point of view, mounting evidence suggest that the prefrontal cortex, including the dorsal ACC generates error-related midfrontal theta/ERN as a low-level mismatch between the actual and expected response (Cavanagh et al, 2014; Jocham & Ullsperger, 2009; Parker et al, 2005; Ridderinkhof et al, 2004b). On the other hand, less clear is the origin of the Pe, which has been associated with the engagement of different areas such as the anterior parts of the ACC (Holroyd & Coles, 2002), posterior portions of the cingulate (Vocat et al, 2008) and insular cortices (Klein et al, 2013), which in turn have been associated to the salience network (Lenzoni et al, 2021; Orr et al, 2011; Wessel, 2017); the Pe/oPe seem to signal the awareness of an error, following motivational and affective events, and may be link with post-error adaptation (Overbeek et al, 2005; Danielmeier & Ullsperger, 2011). The distinct cortical involvement of these error-related responses is in line with evidence suggesting the existence of independent mechanisms underlying the error monitoring system (di Gregorio et al, 2018; Steinhauser & Yeung, 2010), that seem also to rely on distinct neurotransmitters (Falkenstein et al, 2005; Holroyd & Coles, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers believed that ERN combined with Pe can deepen the understanding of ERN understanding [3]. Some scholars have presented both ERN and Pe in their research results [29,30]. ERN had been proposed to reflect early performance monitoring and error detection, while Pe had been connected to subsequent error awareness [31].…”
Section: The First Experiments For Mental Fatigue and College Athlete...mentioning
confidence: 99%
“…Similarly, self-awareness manifest through metacognition is not exclusively a higher-order process, since it involves early 'preconscious' representations, apparent for example in electrophysiological signatures of error-monitoring, such as the early error-related negativity (ERN) and subsequent error positivity (Pe), which can be selectively compromised in neurological disorders [48]. Homologous mechanisms are shown to operate also in non-human primates [49], and, in humans, the Pe is associated with both awareness of error and accompanying psychophysiological responses [50].…”
Section: Levels Of Self-awarenessmentioning
confidence: 99%